2016
DOI: 10.1165/rcmb.2016-0019ps
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Mechanisms of Airway Hyperresponsiveness in Obese Asthma

Abstract: Obesity affects the incidence and severity of asthma in at least two major phenotypes: an early-onset allergic (EOA) form that is complicated by obesity and a late-onset nonallergic (LONA) form that occurs only in the setting of obesity. Both groups exhibit airway hyperresponsiveness to methacholine challenge but exhibit differential effects of weight loss. Measurements of lung function in patients with LONA obese asthma suggest that this group of individuals may simply be those unlucky enough to have airways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…The same mechanism is suggested for the decrease in IC [9]. In our study, a more pronounced bronchial obstruction was in obese asthmatics with FEV 1 67.8 ± 2.1 % compared to those without obesity 74.9 ± 2.4 %, P < 0.05 that can be explained by a higher degree of bronchial hyperreactivity in BA-obesity phenotype [10]. The literature indicates that even obese non-asthma tics may have a significant airway obstruction due to small airway collapse when lung volume is reduced [11].…”
Section: Discussionsupporting
confidence: 83%
“…The same mechanism is suggested for the decrease in IC [9]. In our study, a more pronounced bronchial obstruction was in obese asthmatics with FEV 1 67.8 ± 2.1 % compared to those without obesity 74.9 ± 2.4 %, P < 0.05 that can be explained by a higher degree of bronchial hyperreactivity in BA-obesity phenotype [10]. The literature indicates that even obese non-asthma tics may have a significant airway obstruction due to small airway collapse when lung volume is reduced [11].…”
Section: Discussionsupporting
confidence: 83%
“…High BMI can affect the frequency dependence likely indicative of obesity causing peripheral airway closure and hence, heterogeneity. 75,[94][95][96] The CV 5 is 11%, less than 15%, and hence the study is of acceptable quality. The R 5 is significantly above the reference value for a normal subject's R 5 with a Z-score over 3.…”
Section: Copd With Emphysemamentioning
confidence: 96%
“…As detailed elsewhere in this issue (54,55), obesity has been associated with a greater prevalence and severity of asthma in human populations, and recent studies have strongly suggested that these associations reflect a causal connection, because weight gain has been shown to increase the risk of incident asthma and its severity (56,57), whereas weight loss may ameliorate this effect (58,59). Recent clinical studies have yielded tantalizing insights as to the possibility that "obese asthma" may reflect at least two distinct allergic and nonallergic phenotypes (60) and have suggested a differential role for discrete elements of the metabolic syndrome in altering both the innate and the adaptive arms of the immune response in asthma (61).…”
Section: Asthmamentioning
confidence: 98%